Effectiveness of the Spiritual-Islamic Healing Group Therapy on Increasing the Resilience and Life Expectancy of Veterans with Mental Disorders - A. Afshari (Afarand Scholarly Publishing Institute, 2019)
Aim(s): The war and its resulting stresses caused mental disorders as a prevalent problem in disabled veterans and their families. The aim of this study was to investigate the effectiveness of the spiritual-Islamic healing group therapy on increasing the resilience and life expectancy of veterans with mental disorders. Instruments & Methods: This semi-experimental study with the pretest-posttest design was carried out on 30 people of veterans with mental disorders in Maragheh city in 2018. The subjects were selected by convenience sampling method and randomly assigned in to the two control and experimental groups (n=15 in each group). The research instruments were the Connor-Davidson resilience scale and Schneider life expectancy scale. The spiritual-Islamic healing group therapy was implemented for the experimental group in 8 sessions-in 90 minutes during the 10 weeks. Data were analyzed through SPSS 21 software using multivariable analysis of covariance test (MANCOVA). Findings: By controlling the effect of the pretest, there was a significant difference between the mean scores of the posttest stage in the life expectancy and resilience in the control and experimental groups. After the intervention, the mean scores of these variables in the experimental group was higher than the control group (p<0.05). Conclusion: The spiritual-Islamic healing group therapy improves the resilience and life expectancy in veterans with mental disorders.